2008
DOI: 10.4161/auto.5552
|View full text |Cite
|
Sign up to set email alerts
|

NIX induces mitochondrial autophagy in reticulocytes

Abstract: The controlled elimination of defective mitochondria is necessary for the health of long-lived post-mitotic cells, like cardiomyocytes and neurons. Mitochondrial elimination also occurs during the course of normal development, in lens epithelial and erythroid cells. Strikingly, at the final stage of erythroid cell maturation, newly formed erythrocytes, also known as reticulocytes, eliminate their entire cohort of mitochondria. We have employed this model to investigate the mechanism of programmed mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 22 publications
2
63
1
Order By: Relevance
“…17 We hypothesized that the degradation may be occurring along an autophagy-lysosomal pathway, because previous studies have suggested that depolarized mitochondria can be targeted for mitophagy in mammalian cells. [19][20][21][22] Consistent with this hypothesis we observed greater colocalization between GFP-LC3 and mitochondria in HeLa cells following ectopic expression of Parkin. In addition, we found that Parkin-induced mitochondrial degradation is substantially reduced in Atg5 -/-mouse embryonic fibroblasts (MEFs) compared to wild-type MEFs; and mitochondrial degradation in HeLa cells is reduced by 3-methyladenine, an inhibitor of autophagy, or bafilomycin, an inhibitor of lysosomal degradation.…”
Section: Parkin Induces Mitophagy Following Depolarizationsupporting
confidence: 77%
“…17 We hypothesized that the degradation may be occurring along an autophagy-lysosomal pathway, because previous studies have suggested that depolarized mitochondria can be targeted for mitophagy in mammalian cells. [19][20][21][22] Consistent with this hypothesis we observed greater colocalization between GFP-LC3 and mitochondria in HeLa cells following ectopic expression of Parkin. In addition, we found that Parkin-induced mitochondrial degradation is substantially reduced in Atg5 -/-mouse embryonic fibroblasts (MEFs) compared to wild-type MEFs; and mitochondrial degradation in HeLa cells is reduced by 3-methyladenine, an inhibitor of autophagy, or bafilomycin, an inhibitor of lysosomal degradation.…”
Section: Parkin Induces Mitophagy Following Depolarizationsupporting
confidence: 77%
“…40 Nix was therefore suggested to be essential for the loss of mitochondrial membrane potential, which would act as a signal to target mitochondria for autophagy. 40,41 In agreement with this, Nix was recently found to bind the mammalian Atg8 homologues MAP1-LC3 and GABARAP and thus recruit forming autophagosomes to depolarized mitochondria 42 (Fig. 1); as such Nix may represent the closest mammalian homologue of the yeast Atg32, 37,42 at least in erythroid mitophagy.…”
Section: The Role Of Mitophagy In Red Blood Cell Maturationmentioning
confidence: 60%
“…39 Importantly, mitochondria within wild type reticulocytes depolarize during their maturation, while those in Nix -/-reticulocytes maintain their membrane potential. 40,41 Mitochondrial clearance is restored in Nix -/-reticulocytes in which the loss of mitochondrial membrane potential is chemically induced. 40 Nix was therefore suggested to be essential for the loss of mitochondrial membrane potential, which would act as a signal to target mitochondria for autophagy.…”
Section: The Role Of Mitophagy In Red Blood Cell Maturationmentioning
confidence: 99%
“…This enhancement of autophagy correlated with reduction in BNIP3-mediated cell death. 48 Apart from its function in apoptosis, Zhang and Ney (2008) found that Nix does not mediate the induction of autophagy in erythrocytes, but obviously is required for the selective incorporation of mitochondria into autophagosomes. 49,50 Thus, Nix protein is well known for its participation in apoptotic processes within the cell.…”
Section: Methodsmentioning
confidence: 99%